HUBUNGAN POLA ASUH ORANG TUA DENGAN KONSEP DIRI PADA REMAJA AWAL USIA 10 – 12 TAHUN DI DESA KEDUNGMALING KABUPATEN MOJOKERTO - Kusmindarti, Indah; Zain Karismulo, Aqib (JURNAL KEPERAWATAN SEHAT, 2016)
Parenting is a process in a family, the interaction between parents and their children. Parenting has been applied since the child was born and adjusted in accordance with the ago and stage of development, for example in children agod 10 12 years. The mentioned age is the preadolescent’s period that has various development characteristics that will affect an individual perspective. Individual knowledge about them selves, the combination of feelings, attitudes, and perceptions are labeled as self-concept. Individual knowledge about themselves, the combination of feelings, attitudes, and perceptions are labeled as self-concept. This study aimed to determine the correlation between parenting style of parent with school-age child’s self concept (10-12 years). The type of research was the non-experimental quantitative with correlation study and data colletion using questionnaires respondents is this research were children aged 10-12 years and determined by total sampling technique. Total respondent were 60 people. The variables in this study are parenting parents as independent variables and self-concept of children of school age (10-12 years) as the dependent variable. Data were verified by using chi square and the results showed that where was correlation between parent’s parenting style with school-age child’s self concept 10-12 years (p=0,044). It the authoritatif parenting, more children were found with positive self-concept 68.6%, while the authoritarian and permissive parenting got more children with negative self –concept that was 83.3% and 33.3%. it was suggested that parents should apply authoritatif parenting where children 10-12 years old with the most positive self –concept are derived from the style, with the interests and abilities community nurses is expected with their role in the community to be able to help locate the problem and provide health educatio related to parenting style and children’s self-concept.Key words : parenting, self-concept, adolescent